2014
DOI: 10.1016/j.micres.2013.09.019
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial community structure and its regulating factors in the intertidal sediment along the Liaodong Bay of Bohai Sea, China

Abstract: Investigating the entire species composition of the microorganisms is crucial to understand their roles in the biogeochemical cycles. Metagenomic DNA was extracted from six intertidal sediment samples along the Liaodong Bay of Bohai Sea, China, and was sequenced which yielded a total of 64,496 high-quality sequences from 83,485 reads, with an average read length of 463 bp. The sequences were assigned to 20,718 operational taxonomic units (OTUs) which belong to 42 phyla, 90 classes and 376 genera. At the differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
48
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(56 citation statements)
references
References 50 publications
8
48
0
Order By: Relevance
“…Our results showed that the microbial diversities were high in the intertidal sediments of Sansha Bay, with a average of 3766 ± 76 OTUs per sample. The Shannon index (varied between 6.72 and 6.9, Table 3) was comparable and a slightly lower than previous studies in intertidal sediments in Liaodong Bay (6.72-7.54, Zheng et al, 2014), and Bohai Bay (7.17 and 7.19, Wang et al, 2013), China.…”
Section: Microbial Community Structure In Mudflat Sediments In Sanshasupporting
confidence: 78%
“…Our results showed that the microbial diversities were high in the intertidal sediments of Sansha Bay, with a average of 3766 ± 76 OTUs per sample. The Shannon index (varied between 6.72 and 6.9, Table 3) was comparable and a slightly lower than previous studies in intertidal sediments in Liaodong Bay (6.72-7.54, Zheng et al, 2014), and Bohai Bay (7.17 and 7.19, Wang et al, 2013), China.…”
Section: Microbial Community Structure In Mudflat Sediments In Sanshasupporting
confidence: 78%
“…studies of bacterial communities have focused upon cultureindependent molecular techniques, for instance, quantitative PCR (qPCR), denaturing gradient gel electrophoresis (DGGE), clone library and the next generation sequencing (NGS), that circumvent the limitations of cultivation. The NGS technologies, such as 454 pyrosequencing, have recently become more and more popular among microbiologists investigating microbial community structures (Zheng et al 2014;Song and Wang 2015). Pyrosequencing is powerful for detecting microbial diversity, even the rare species, thereby providing a deep insight into the microbial communities (Huber et al 2007;Zheng et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Microbes regulating and influencing many ecosystem processes such as nutrient transformation and organic matter decomposition [2] could function as potential bio-indicators of pollution and environmental variation. All of this makes a freshwater sediment system a suitable environment to study the mechanism of complex geochemical recycling processes.…”
mentioning
confidence: 99%